2020
DOI: 10.3390/su12166322
|View full text |Cite
|
Sign up to set email alerts
|

Pay for Individual Performance: Aiding or Harming Sustainable Intrinsic Motivation?

Abstract: This study aims to understand the effect of pay for individual performance (PFIP) on employees’ intrinsic motivation. Although several studies have analyzed this relationship, until now, the role of satisfaction with variable rewards has not been considered. It was hypothesized that employees who are satisfied with variable rewards would find in PFIP a source of feedback that would contribute to the satisfaction of their basic psychological needs. An empirical study was conducted with 184 professionals working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Compensation significantly affects job satisfaction. This is in line with previous research reports (Cabanas et al, 2020;Saluy, Raharjo, 2021;Shen et al, 2017), which show that the alignment between the compensation system and the expectations of workers plays a role in increasing job satisfaction so that workers will feel calm at work.…”
Section: The Effect Of Compensation On Job Satisfactionsupporting
confidence: 92%
“…Compensation significantly affects job satisfaction. This is in line with previous research reports (Cabanas et al, 2020;Saluy, Raharjo, 2021;Shen et al, 2017), which show that the alignment between the compensation system and the expectations of workers plays a role in increasing job satisfaction so that workers will feel calm at work.…”
Section: The Effect Of Compensation On Job Satisfactionsupporting
confidence: 92%
“…When employees perceive PFP as information, their interest in the work itself increases, which is called "intrinsic motivation" in motivation research. Several studies confirmed that PFP enhances intrinsic motivation (Cabanas et al, 2020). Hackman and Oldham (1975) suggested that intrinsic motivation significantly influences employees' behaviors and attitudes.…”
Section: The Emerging Importance Of Cognitive Evaluation Theorizing I...mentioning
confidence: 92%
“…All returns employees receive due to their job are referred to as employee compensation (Dessler 2015;Cabanas et al 2020). The literature on self-determination theory (SDT) claims that compensation systems serve as significant external triggers (Ryan and Deci 2017;Tepliuk et al 2021).…”
Section: Compensation Systemmentioning
confidence: 99%